Creating Safe and Empowering Schools: Implementing the Human Security Framework as a Catalyst for Achieving the SDGs - Farhana, Husna; Widiansyah, Apriyanti; Maharbid, Dian Anggraini (International Conference on Elementary Education, 2025)
The SDGs agenda emphasizes an inclusive and holistic development approach. Although SDG 4 (Quality Education) plays a key role, traditional approaches often focus solely on access and infrastructure, failing to address the multidimensional threats faced by school members. This studyproposes the Human Security framework, encompassing economic, food, health, environmental, personal, community, and political security, as an operational strategy to simultaneously advance theachievement of various SDG targets Based on a qualitative case study at SDN Bahagia 05 Bekasi, data was collected through observation, interviews, and document analysis. The results show that the implementation of human security was realized through programs such as: an anti-bullying system and counseling (SDGs 3,4,16), a healthy canteen and health education (SDGs 3,4), the Adiwiyata (environmentally-friendly school) program and inclusive classrooms (SDGs 4,11,13), peer mediation and parental participation (SDGs 4,16), scholarships and student entrepreneurship (SDGs 1,4,8), as well as guarantees of healthy food (SDGs 2,3,4) and political security (SDGs 4,5,10,16).integrating human security transforms schools into not only safe and comfortable learning environments but also empowering agents of change. This approach proves strategic for achieving not just SDG 4, but also for fostering progress in other goals such as poverty eradication, good health, gender equality, and peace. Therefore, a human security perspective needs to be adopted in national and local education policies